Pendampingan Perencanaan, Pengelolaan dan Evaluasi Pembelajaran Berbasis Proyek Bagi Guru Matematika SMK Kota Mataram - Baidowi Baidowi; Dwi Novitasari; Sri Subarinah; Ratih Ayu Apsari; Ni Made Intan Kertiyani (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
This community service activity aims to provide assistance to SMK teachers in Mataram City in developing project-based learning to design, implement, and evaluate project-based mathematics learning. The specific target to be produced from this service activity is the optimal understanding of SMK teachers throughout the city of Mataram related to the planning, implementation, and evaluation of project-based mathematics learning. To achieve this target, mentoring was carried out for SMK teachers in Mataram City, each represented by 2 teachers in each partner school. Mentoring activities are carried out with a series of activities, namely (1) Seminars related to the general description of project-based learning and dissemination of research results that are still related to the need for project-based learning to be implemented in schools, (2) Workshop on project-based learning design, (3) Workshop on implementation project-based learning, (4) project-based learning evaluation workshops, (5) forum group discussion results from the implementation of activities in each school. The results of the service activities showed a positive response from the training participants and an increase in participants' understanding of project-based learning in mathematics learning.